Clinical, dermatoscopic and pathomorphological differential diagnosis of pigmented and pigmented melanoma of the skin - E. Yu. Neretin; K. S. Titov; M. V. Sorokina; T. A. Yakusheva; G. N. Kozlov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. The study of pigmented melanoma of the skin is an urgent problem today, because this pathology has an aggressive course, frequent localization on the skin, rare occurrence – no more than 2-8% among other malignant neoplasms of the skin, while it is difficult to diagnose clinically, pathohistologically.The purpose of the study: to study the clinical, dermatoscopic and pathomorphological diagnosis of pigmented and pigmented melanoma of the skin. As tasks, the possibilities of diagnosing pigmented and pigmentless melanoma of the skin at the stage of consultation, as well as the features of the use of light microscopy and immunohistochemical examination by pathologists were studied.Material and technical base: Delta Heine 20 dermatoscope, Carl Zeiss Axio Scope A2 light microscope, evaluation of results according to clinical recommendations. As a result of the study, it was revealed that the diagnosis of pigmented, unlike pigmented, melanoma of the skin is difficult due to the lack of characteristic signs. It was concluded that it is advisable to use digital dermatoscopy at the clinical stage; an immunohistochemical examination should be used by a pathologist; if there is doubt about the goodness of the process, an incisional biopsy of the neoplasm with a pathohistological examination is required.